Microwave irradiation optimization for efficient lignin removal from cocoa shell waste using alkali - Farah Hafidzah, Ahmad; Nurhamizah, Ibrahim; Mohd Sabri, Mahmud; Ali, Waleed; Mohd Bijarimi, Mat Piah; Suriyati, Saleh; Said, Nurdin (IIUM, Malaysia, 2021)
This paper reports a study to determine the optimum conditions of microwave in assisting alkali treatment for removing lignin from cocoa shell waste (CSW). The CSW was mixed with 5% of NaOH solution at the ratio of 1: 10 of weight to volume of the alkaline before being irradiated in a microwave oven. Various microwave powers (200-400 W), temperature settings (60-80 °C) and irradiation times (10-20 min) were tested on 15 samples set by the Box-Behnken design. The lignin removal was analysed using a 72 % sulfuric acid treatment method. A quadratic equation was employed to the response surface and statistical analysis conducted to confirm the adequacy of the model. The plots show that the optimum microwave conditions are 400 W, 76 °C and 19 min, which were capable to remove 86.57% of lignin. Thermogravimetric analysis and micrographs revealed different decomposition temperature of lignin and morphology of extensively-pored surface of treated CSW, respectively.